PENDAMPINGAN KELUARGA UNTUK MENINGKATKAN KEPATUHAN PASIEN DALAM PENANGANAN TUBERKULOSIS PARU - Supriadi, Supriadi; Kamil, Mustofa; Pramudia, Joni Rahmat; Saripah, Iip (Poltekkes Kemenkes Bandung, 2024)
This research stems from various policies that have been implemented by the government to eradicate and prevent pulmonary tuberculosis which still does not show optimal results. The main obstacles are poor patient compliance and suboptimal family support. Efforts to improve patient compliance in handling pulmonary tuberculosis are not only imposed on health care providers, families and patients are also responsible for this. This study aimed to determine the effect of family assistance on increasing patient compliance in handling pulmonary tuberculosis. The study was conducted from October 2, 2023-January 2024 in Dunguscariang Village, Garuda Community Health Center Working Area, Bandung City. This study used quasi-experimental pre-test and post-test design methods, sampling in total with the criteria of families who have pulmonary tuberculosis patients, so that 37 families were obtained in Dunguscariang sub-district as an intervention group and 39 families as a control group in Garuda Kota Bandung sub-district. Data were collected through interview techniques using the morisky medication adherence scale 8 adherence instrument. Data analysis using dependent- T test. The results showed an increase in the average adherence score between before and after family assistance and showed that family assistance had a significant effect on increasing patient compliance in handling pulmonary tuberculosis. Constructed family assistance can improve patient compliance in handling pulmonary tuberculosis with three elements, namely enable, empowering and protecting.